Biomass Yield of Warm‐Season Grasses Affected by Nitrogen and Harvest Management. (1st May 2018) - Weerasekara, Chamara S.; Kitchen, Newell R.; Jose, Shibu; Motavalli, Peter P.; Bardhan, Sougata; Mitchell, Robert B.
Abstract : Core Ideas: Dry matter yields increased with N inputs although efficiency decreased. Applying nitrogen at 67 kg N ha –1 was superior in both yield and efficiency. Delaying the time of harvest until late fall or a killing frost increased yield. Native perennial warm‐season grasses (NPWSG) have drawn interest as bioenergy feedstocks due to their high productivity with minimal amounts of inputs under a wide range of environments. Nitrogen fertility and harvest timing are critical management practices when optimizing biomass yield of NPWSG. Our objective was to quantify the impact of N fertilizer rate and timing in combination with harvest timing and frequency on NPWSG yield. Research was conducted in 2014 and 2015 on four field‐plot locations in Missouri. The experiment was a split‐plot design with three replications where N rate and harvest timing were the main and sub‐plot treatments, respectively. Nitrogen rates were 0, 34, 67, and 101 kg N ha −1 with two application timings, all early spring and split N (early spring and following first harvest). Harvest timing included two single (September and November) and two double harvests (June followed by September or November) per year. Delaying harvest until November increased yield across sites. November harvest and N rates ≥67 kg ha −1 improved NPWSG biomass yields. Although N fertilization improved yield, partial factor productivity (PFP) of applied N did not increase with annual N rates >34 kg ha −1 . Fertilization at 67 kg ha −1 yr −1 provides an opportunity to maintain a balance between yield and N efficiency. These results demonstrated that N fertilization and harvest management of NPWSG were not always independent, and therefore these practices should be simultaneously considered. For example, early‐season harvesting suppressed response to N when the second harvest was not delayed until after frost.